High bioreactor production and emulsifying activity of an unusual exopolymer by Chromohalobacter canadensis 28 - TOKSOY ÖNER, EBRU (WILEY, 2020)
Unusual composition of an exopolymer (EP) from an obligate halophilic bacterium Chromohalobacter canadensis 28 has triggered an interest in development of an effective bioreactor process for its production. Its synthesis was investigated in 2-L bioreactor at agitation speeds at interval 600-1000 rpm, at a constant air flow rate of 0.5 vvm; aeration rates of 0.5, 1.0, and 1.5 vvm were tested at constant agitation rate of 900 rpm. EP production was affected by both, agitation and aeration. As a result twofold increase of EP yield was observed and additionally increased up to 3.08 mg/mL in a presence of surfactants. For effective scale-up of bioreactors mass transfer parameters were estimated and lowest values of K(L)a obtained for the highest productivity fermentation was established. Emulsification activity of EP exceeded that of trade hydrocolloids xanthan, guar gum, and cellulose. A good synergism between EP and commercial cellulose proved its potential exploration as an enhancer of emulsifying properties of trade emulsions. A pronounced lipophilic effect of EP was established toward olive oil and liquid paraffin. Cultivation of human keratinocyte cells (HaCaT) with crude EP and purified gamma-polyglutamic acid (PGA) showed higher viability than control group.
Keywords: agitation and aeration; biocompatibility; emulsifying properties; exopolymer; halophilic bacterium; EXOPOLYSACCHARIDE PRODUCTION; AGITATION SPEED; AERATION; OPTIMIZATION; EPS